RELATIONSHIP BETWEEN STRESS LEVELS AND CHANGES IN RANDOM SUGAR LEVELS IN PATIENTS WITH DIABETES MELLITUS AT MENTIKAN PUBLIC HEALTH CENTER, MOJOKERTO CITY - Wahyuni, Lutfi; Krisnana, Ilya; Ramadina, Rizma Dwi (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
Diabetes mellitus is a metabolic disease characterized by randomly high blood sugar levels. Risk factors that can cause diabetes mellitus include stress, genetic factors, age, and a history of consuming alcohol. The simplest effort to control random blood sugar is by implementing stress management. But in reality, there are still many diabetes mellitus sufferers who cannot manage stress, resulting in random increases in blood sugar levels. This study aims to determine the relationship between stress levels and changes in random blood sugar levels in diabetes mellitus sufferers in the Mentikan Community Health Center, Mojokerto City. This research uses a correlation analytical method with a cross-sectional design. The total sample was 67 respondents taken using the purposive sampling technique. The Spearman Rho test results showed a value of 0.001 < α 0.05, so it can be concluded that there is a relationship between stress levels and random changes in blood sugar levels in diabetes mellitus sufferers. Meanwhile, the correlation coefficient figure shows a value of 0.663, which means the relationship between stress levels and random changes in blood sugar levels is strong. Stress can increase random blood glucose levels because stress stimulates the body to release the hormones cortisol and epinephrine. These two hormones have a strong effect in causing the process of gluconeogenesis, so that it will increase random blood glucose levels by large amounts within a few minutes. It is hoped that good stress management can control sufferers' sugar levels so as to create a better quality of life for Diabetes Millitus sufferers.